Comparison of serum homocysteine level among preeclamptic and normotensive pregnant women: a case-control study in a tertiary care hospital - Ananthathirtha, Kavya; Raghuveer, Pracheth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: It has been postulated that hyperhomocysteinemia may be associated with preeclampsia, as the vascular changes mediated by homocysteine are similar to the changes that occur in preeclampsia. In this context, the study was conducted to compare maternal serum levels of total homocysteine in preeclamptic and normotensive pregnant women attending a tertiary care hospital in Coimbatore, Tamil Nadu, India. Methods: A prospective case-control study was carried out in the inpatient wards and the outpatient department (OPD) of the Department of Obstetrics and Gynaecology (OBG) at a tertiary care hospital of Coimbatore, for one year from March 2015 to April 2016. Pregnant women with preeclampsia were considered as cases and women without any medical or other obstetric and fetal complications were selected as controls. A pre-designed and pre-tested proforma was used to collect the appropriate information. The assessments were conducted using standard procedures. Results: The study population comprised of 50 cases and equal number of controls. Around 28.0% of the cases had severe preeclampsia. The mean serum homocysteine values among cases was 13.87±4.01 µmol/L. The difference in the mean serum homocysteine level among cases and controls was statistically significant (p <0.001). However, there was no significant difference in the mean serum homocysteine levels among women with severe and mild preeclampsia (p=0.731). Conclusions: Maternal serum levels of total homocysteine were found to be significantly higher among preeclamptic women when compared to normotensive women. Thus, estimation of serum homocysteine levels among preeclamptic women may serve as a biomarker for identifying those at risk for complications.